Evaluation of cuprohca® as an alternative to the copper sulphate footbath - Yanmaz, Latif Emrah (The Philippine Journal of Veterinary Medicine, 2022)
The aims of this study were to determine the effective ratio of a new commercial footbath, namely CuproHCa®, against bacterial load and to reveal the number of cows that could pass from the ideal concentrations of CuproHCa® footbath solution without disrupting the effectiveness relative to copper sulphate (CuSO4). A total of 80 Holstein Friesian cows under each footbath regimen walked in the footbath twice a day after four consecutive milkings. After every 10 passes from the footbaths, 33 samples for each solution totalling 66 samples were subjected to pH, oxidation reduction potential (ORP), microbiological, and volumetric analysis. The pH value was 4.08 after 230 cows passed through in CuSO4, whereas pH value in CuproHCa® footbath showed minimal change over time (1.90±0.08). The overall ORP value of CuproHCa® (343.21±12.31 mv) was higher than CuSO4 (294.97±61.40 mv, p<0.001). The overall bacterial load of CuproHCa® (0.44±0.18 ng/ml) was higher than CuSO4 (0.37±0.21 ng/ml, p=0.007). The volumetric copper analysis in CuproHCa® (10.02±0.81) was higher than CuSO4 (9.22±0.84), (p<0.001). In conclusion, based on pH and ORP analysis, 10% CuproHCa® has less effect compared to 4% CuSO4. After 280 cows passed through the footbath, CuproHCa® has a better antibacterial effect than CuSO4.